ANALISIS KUALITAS PRODUK PENYAMAKAN KULIT DENGAN METODE SQC dan FMEA - Saputra, Anang Dwi Saputra; Andung Jati Nugroho (Lembaga Pengembangan Kinerja Dosen, 2023)
PT Adi Satria Abadi is a company engaged in tanning. The problem faced by the company is the presence of defective leather during the goat and sheep tanning production process. From these problems, the purpose of this study was to identify the level of product defects, analyze the factors that cause defects, and make recommendations for improvements to improve the quality of goat and sheep tanning products. Data processing in this study uses the SQC (Statistical Quality Control) and FMEA (Failure Mode and Effect Analysis) methods. Based on the identification results, it was found that there were 1,507 holes for holes, 1,066 for thick defects, 1,061 for louse defects, and 1,086 for size defects. The results of the SQC analysis still have uncontrolled data based on the control chart which is on size defects with a total of 1,086 defects, while for hollow defects, too thick defects, and tick defects are under control. The results of the FMEA analysis show that the order of completion with the first priority is spotting bugs with an RPN value of 36. The suggested improvements to the company are by directly selecting raw materials and supervising employees. Keywords: Quality, Product Defects, Seven Tools, SQC, FMEA.